법 앞에 ‘얼짱’은 유리한가? 루틸리아나의 원상회복 청구 사건 - 최병조(Choe, Byoung Jo) (법사학연구, 2010)
이 글은 <학설휘찬> D.4.4.38.pr에 전하는 Rutiliana의 원상회복 청구 사건을 다룬 것이다. 이것은 황제의 고문회의에서 논의된 후 황제에 의해 재결이 나온 실제 사건이었는데, 중세 이탈리아의 법률가들이 관련 당사자 루틸리아나의 美貌를 언급하면서 그 배경에 관심이 쏠리게 되었는데, 현대 독일의 두 로마법 연구자가 서로 상반된 해석을 전개하여 다시금 관심을 불러 있으켰던 적이 있다. 매매대금 지급 불이행시 매도인에게 계약 해제권을 유보시킨 조항(lex commissoria)의 효력을 둘러싸고 매수인의 미성년 상속인이 제기한 원상회복 신청이 제1심과 제2심 그리고 황제 고문회의 위원이었던 Paulus의 법률논리대로 처결되지 않고 황제의 특별한 배려로 결정이 된 사안이라는 점에서 당시 법운영의 일단을 잘 보여주는 반면, 정작 ‘美貌’의 정체는 13세기 Odofredus의 근거 없는 창안임이 밝혀졌다. This paper analyzes the real case of Rutiliana before the Emperor which Paulus D.4.4.38.pr reports. Aemilius Larianus bought from Ovinius the Rutilian land under a lex commissoria and paid part of the price, the conditions being that if he did not pay half of the rest of the price within two months of the sale, the contract should be at an end, and likewise that if he had not paid the balance of the price within further two months, the contract similarly would be at an end. Within the first period of two months, Larianus died and was succeeded by Rutiliana, a pupilla whose tutors failed to make the payments due. The seller, having given frequent warnings to the tutors, after a year sold the same land to Claudius Telemachus. The pupilla sought restitutio in integrum. Having lost in the proceedings both before the praetor and the urban prefect, she appealed. From the beginning of the debate in the consilium principis the emperor did not share the opinion of Paulus. The jurist thought that the judgments of the lower instances were correct because the contract had been made by her father and not by the pupilla herself. However, the emperor was swayed by the fact that the day on which the sale might be rescinded fell in the time of the pupilla, and on that ground, as he seemingly thought, the conditions of the sale were not observed. Paulus, now becoming concessive to the emperor, demanded though strongly that a better reason for granting restitutio would be that the seller, by giving warning after the day on which it had been agreed that the sale might be rescinded and by seeking the price, is held to have departed from his own condition. He also maintained firmly that it did not matter that the time had run out after the death of the father, any more than if a creditor had sold a pledge when the day for the payment had passed after the death of the debtor. Nevertheless, because the lex commissoria displeased him, the emperor awarded restitutio in integrum. He was also influenced by the fact that the former tutors who had not sought restitutio had been declared suspect. In this case the Roman jurists as usual are concerned only with the legal issues it brings about. It is, however, imbued in a very unique way with old comments which threw for the first time the beauty of the girl into the scale. In the thirteenth century Italian jurists (Odofredus and Vivianus) proposed this new reason for the emperor’s sentence which obviously deviated from the standard legal practice of the time. In late seventies of the last century Detlef Liebs and Berthod Kupisch, both Roman law professors of Germany, discussed on the issue and produced two completely divergent interpretations. I am on the whole, agreeing to Liebs, being very sceptical about the exegesis of Kupisch. It is, as a matter of fact, not to be proved whether or not the girl was beautiful. The debate in the consilium demonstrates that the Roman jurists came to the decision on the basis of rational argumentation supported by established principles and rules of law, ohne Ansehung der Person (Deuteronomium 1:17, 16:19):“Vous n’aurez point égard à l’apparence des personnes dans vos jugements.” KCI Citation Count: 0